Analisis Krisis Stok dan Melonjaknya Harga Minyak Goreng di Kota Medan - Lady Christine Elizabeth Br Jawak; Reni Rasnita Manurung; Rika Risgita Br Ginting; Shana Audryetta Situmorang (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to analyze the scarcity and rising prices of cooking oil in Medan. The research method used in this study is a qualitative descriptive research method. The data analysis technique in this study refers to the Miles and Huberman model. Miles and Huberman state that the Analysis Interactive Model technique has several stages: data collection, data reduction, data display, and conclusions. The results showed that there were 4 factors causing the stock crisis and soaring cooking oil prices in Medan: (1) The international war between Russia and Ukraine which affected CPO exports and imports, and resulted in CPO entrepreneurs selling abroad because the price was higher than the domestic; (2) Government policies regarding B30; (3) Panic buying or it can also be called buying in large quantities among the people of the city of Medan; (4) There has been an increase in MSME traders using cooking oil in Medan.